Repeated-sprint training in hypoxia in international rugby union players - Beard, A.; Ashby, J.; Chambers, R.; Brocherie, F.; Millet, G. P. (International Journal of Sports Physiology and Performance, 2019)
Rugby union is an intermittent sport often having periods of high-intensity efforts with incomplete recoveries. Total distances reported in the literature have ranged between 4800 and 5200 m for forwards and 5600 and 6000 m for backs, whereas sprint distances have ranged between 350 and 510 m. Furthermore, it has been demonstrated in other similar team sports, such as rugby league, that as the level of competition rises from nonprofessional to professional level, the requirement for a higher number of sprints and need for higher strength and power abilities becomes paramount to game performance. Rugby union`s international competitions tend to have small (ie, 1-2 wk) transition periods from national clubs to international games; this can pose problems for coaches and strength and conditioning experts in preparing players adequately. The search for useful methods that are able to shorten adaptation times within these small preparation periods from different levels of competition could provide a potential edge for physical performance. It was recently found that RSA performance was improved after a 2-week intensified training period with elite soccer players after competition. This may have good carryover to rugby union, which has a high number of repeated-sprint requirements.